A Novel Study On Biogas Production From Palm Oil Mill Effluent With Two-Stage Anaerobic Digester And Nano Membrane - M. Shahidul, Islam; Malcolm, M. L.; Eugene, J. J.; Sharafatul, M.I (Science International, 2019)
This paper describes the problem of poor treatment performance of palm mill effluent (POME); and also presents an economically and environmentally sustainable solution achieved from an experimental research. This research investigates the effects of organic loading rate (OLR), hydraulic retention time (HRT), sludge retention time (SRT), pH, and carbon to Nitrogen ratio (C/N) as the input factors with the Nano membrane that contribute to increase biogas production performance. A two-stage continuous stirred tank anaerobic reactor (CSTR) and cross flow membrane have used in series with C/N enriched inoculum for the POME digestion. The anaerobic digester and membrane were operated at temperature 350C with various range of inputs. The research findings demonstrated that OLR,HRT,SRT, and pH have played a significant (p-value<0.05) role in producing biogas with substrate utilization rate 92.50 percent (R 2=92.5), while other inputs used for digestion process were positively affected on the production of biogas and quality effluent. The findings of this research would be useful in palm oil mills for optimizing the production of biogas and recyclable water from the POME as Waste to Resource [WtR]. However, the novelty of this research is to use ‘C/N enriched inoculum (11<C/N< 40) prepared from banana peel in digestion process with two stage CSTR and the cross-flow membrane for increasing POME treatment performance.